Alisma orientalis Beverage Treats Atherosclerosis by Regulating Gut Microbiota in ApoE-/- Mice - Zhu, Boran; Zhai, Yi; Ji, Mengjiao; Wei, Yanan; Wu, Jiafei; Xue, Wenda; Tao, Wei wei; Wu, Haoxin (Frontiers in Pharmacology, 2020)
Background: Alisma orientalis beverage (AOB) is a traditional Chinese medicine formulated with a variety of natural medicinal plants and has long been used for treating metabolic syndrome and atherosclerosis (AS). Given the current limited biological research on AOB, the mechanism by which AOB treats AS is unknown. This study investigated the role of AOB-induced gut microbiota regulation in the development of AS. Methods: We established an AS model in male apolipoprotein E-deficient (ApoE−/−) mice fed a high-fat diet (HFD), administered different interventions and measured serum biochemical indices and inflammatory cytokines. The root of the aorta was stained with oil red O, and the proportion of the lesion area was quantified. Serum trimethylamine (TMA) and trimethylamine N-oxide (TMAO) levels were quantified by liquid chromatography with mass spectrometry. The liver flavin−containing monooxygenase 3 (FMO3) protein expression was confirmed by Western blotting. Gut microbiota composition changes were analyzed using a 16S rDNA sequencing technique. Results: After 8 weeks of HFD feeding, AS development and inflammatory cytokine expression were significantly decreased in mice treated with AOB; the same parameters in the mice treated with the antibiotics cocktail did not change. In the gut microbiota study, mice treated with AOB had a markedly different gut microbiota than the HFD-fed mice. Additionally, AOB also reduced hepatic FMO3 expression and serum trimethylamine N-oxide levels. Conclusion: The antiatherosclerotic effect of AOB is associated with changes in gut microbiota composition and a decrease in TMAO, a metabolite of the gut microbiota, suggesting that AOB has potential therapeutic value in the treatment of AS.